Keabsahan Kontrak Elektronik dalam Transaksi E-Commerce: Fondasi Yuridis, Problematika Pembuktian, dan Urgensi Perlindungan Konsumen Digital di Indonesia - Gilang Rizki Aji Putra; Sri Ajeng Murni Cahyani Putri (BULETIN ADALAH, 2025)
Abstract Electronic contracts form the backbone of e-commerce transactions in digital environments. This article examines the validity of electronic contracts under Indonesian law and identifies challenges in evidence and consumer protection. Using normative legal research, the study finds that the Electronic Information and Transactions Law (ITE Law) recognizes electronic contracts as legally valid and equivalent to conventional contracts under Article 1320 of the Civil Code. However, implementation issues persist, including standard form clauses, weak informed consent through “click-to-accept” systems, and unequal bargaining power. Evidentiary problems regarding authenticity and data integrity also remain. The article concludes that regulatory reform is needed to strengthen meaningful consent and consumer protection. Keywords: Electronic Contracts, E-Commerce, ITE Law, Consumer Protection, Consent.